Mobile Nutrition Dietary Care: Nutrition Support for Cancer Patients: An Integrated Review - FIRDAUS, ROSALIA; Adnurrahman, Khadijah Fatiya; MAWADDAH, SALWA; Maryati, Ida (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The risk of malnutrition in cancer patients is higher than in patients suffering from other diseases. The effect of therapy is the cause of malnutrition problems. The current situation of the COVID-19 pandemic is increasing issues in health systems in various countries, so that the fulfillment of patient needs, especially the need for dietary therapy for chronic diseases such as cancer, is hampered. Objective: This study aims to review the potential of Mobile Nutrition Dietary Care as a nursing model in providing nutritional support for cancer patients during the COVID-19 pandemic to prevent malnutrition based on home care. Method: The method used is an integrative review by searching for study selection results on six databases of 2,697 articles from PubMed, SpringerLink, Cambridge core, NCBI, EBSCO, and Garuda. Results: It found several interventions, such as mobile health, dietary patterns in cancer patients, and the provision of additional nutrition. These interventions are proven to improve the nutritional status of cancer patients. Recommendation: Mobile Nutrition Dietary Care is a nursing model that can support the nutritional status of cancer patients.